Converging forms: an examination of sub-Arctic, circumarctic, and Central Asian Ranunculus auricomus agg. populations - John Paul Bradican; John Paul Bradican; Salvatore Tomasello; Judith Vollmer; Elvira Hörandl (Frontiers in Plant Science, 2024)
IntroductionPhenotypic complexity in species complexes and recently radiated lineages has resulted in a diversity of forms that have historically been classified into separate taxa. Increasingly, with the proliferation of high-throughput sequencing methods, additional layers of complexity have been recognized, such as frequent hybridization and reticulation, which may call into question the previous morphological groupings of closely related organisms.MethodsWe investigated Northern European, Asian, and Beringian populations of Ranunculus auricomus agg. with phylogenomic analysis of 736 genes and 27,586 SNPs in order to deduce the interrelatedness and hybrid origin of this phenotypically and taxonomically complicated group from Europe characterized by a history of hybridization, polyploidy, apomixis, and recent radiation. The ploidy levels and the reproductive mode of the Northern European populations were assessed via flow cytometric seed screening. In addition, in order to examine the phenotypic plasticity of the dwarf forms previously described as species and summarized as the Ranunculus monophyllus group, we conducted climate chamber experiments under cold (northern) and warm (temperate) conditions.ResultsThe Northern European populations are tetra- to hexaploid and propagate primarily through apomixis. The complex is characterized by highly reticulate relationships. Genetic differentiation of the main clusters has occurred between the above-mentioned geographical regions. We find evidence for the hybrid origin of the taxa in these areas with differing genomic contributions from the geographically nearest European sexual progenitor species. Furthermore, polyphyly in the taxa of the R. monophyllus group is supported. Experiments show low lability in the traits associated with the R. monophyllus group.DiscussionWe conclude that multiple adaptations of hybrids to colder climates and shorter vegetation periods have shaped the phenotypes of the R. monophyllus group, and we suggest a formal classification as nothotaxa within the R. auricomus group.